2004
DOI: 10.1088/1126-6708/2004/05/012
|View full text |Cite
|
Sign up to set email alerts
|

Bloch Brane

Abstract: We investigate a system described by two real scalar fields coupled with gravity in (4, 1) dimensions in warped spacetime involving one extra dimension. The results show that the parameter which controls the way the two scalar fields interact induces the appearence of thick brane which engenders internal structure, driving the energy density to localize inside the brane in a very specific way.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
361
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(375 citation statements)
references
References 32 publications
12
361
0
2
Order By: Relevance
“…We should also remark that similar analysis can also be extended for generalized scalar and gravity dynamics [54,57]. Finally apart from the specific directions we have mentioned above the results of this work can find extensions in various aspects of thick brane dynamics including search for particular solutions and probing phenomenology of localized gravity, gauge and matter fields in various geometries [20,58,59,60,61,62,63,64,65].…”
Section: Resultsmentioning
confidence: 56%
“…We should also remark that similar analysis can also be extended for generalized scalar and gravity dynamics [54,57]. Finally apart from the specific directions we have mentioned above the results of this work can find extensions in various aspects of thick brane dynamics including search for particular solutions and probing phenomenology of localized gravity, gauge and matter fields in various geometries [20,58,59,60,61,62,63,64,65].…”
Section: Resultsmentioning
confidence: 56%
“…The richer structure of degenerate and critical Bloch branes where proposed in [49]. In [15] it was shown that the presence of the field χ is crucial to giving internal structure to the brane. In the present work the presence of the field χ also contributes to generate an internal structure to the tube formed.…”
Section: A Tube In (3 1)-dimensionsmentioning
confidence: 99%
“…Usual Newton's law can then be reproduced on the brane depending on the metric warp factor, attained after solving Einstein's equations. Several extensions soon appeared, with smooth thick branes constructed by scalar fields [7][8][9][10][11][12][13][14][15][16]. A comprehensive review on this subject can be found in [17].…”
Section: Introductionmentioning
confidence: 99%
“…A smooth warp factor was investigated? [4][5][6][7][8][9][10][11], but also it did not yield localized gauge fields. Some models obtained the localization by the addition of new degrees of freedom such as a scalar or dilaton fields, but a more natural approach would be to obtain an extension of minimal couplings that would localize the gauge field without introducing other fields.…”
mentioning
confidence: 95%
“…These singularities can be smoothed out through the introduction of kink-like membranes such as in Refs. [5][6][7][8][9] that recovers the RS case only asymptotically. Therefore the best approach is to consider a general warp factor A and to look for a solution to the problem that does not depend on it.…”
mentioning
confidence: 99%